Japanese Abenomics Stimulus Policy: The Impact on Indonesian and Japanese Economy - Setiawan, Sigit (Jurnal Kajian Ekonomi dan Keuangan, 2014)
To address economic crisis and promote domestic economy to re-grow, Japanese government has launched Abenomics stimulus package in January 2013 to be disbursed during period 2013-2014. This study is focused and limited to analyze the impact of Abenomics policy on Japanese GDP and its transmission effect to Indonesian GDP. This study employs quantitative analysis method, completed with descriptive analysis based on historical data and relevant literatures. Main findings from this study are Abenomics will spur Japanese GDP positively by 2,37% in 2013 and by 2,79% in 2014. Spillover effect from Japanese demand shock will bring the biggest impact on the main partner of Asian and Oceania countries, including Indonesia. Indonesia will receive additional positive impact on its growth in 2013-2014 and substractive negative impact during 2015 to early 2017, before bounce back to positive zone in the second quarter 2017 to year 2018.